P43 Complement C3 in diabetes: hypofibrinolysis, glycation and inhibiting interaction with fibrinogen to reduce cardiovascular risk. (26th October 2016) - King, RJ; Schuett, K; Tiede, C; Jankowski, V; John, V; Trehan, A; Simmons, K; Ponnambalam, S; Fishwick, CWG; McPherson, MJ; Tomlinson, DC; Ajjan, RA
Abstract : Aims: Complement C3 compromises fibrin clot lysis but the effect of diabetes on C3 fibrinolytic properties are unknown and fibrinogen interaction sites remain to be elucidated. We investigated i) inter-individual variability in the fibrinolytic properties ofC3 in diabetes ii) binding sites between fibrinogen and C3 and iii) modulation of fibrin clot lysis by manipulating fibrinogen-C3 interactions. Methods: Turbidimetric studies analysed the effect of C3 on fibrinolysis. Mass spectrometry, microarray screening and molecular modelling evaluated C3 glycation and interaction sites with fibrinogen. A novel, non-antibody binding protein (NABP) was used to modulate C3-fibrinogen interaction. Results: C3 from diabetes patients (n = 12) showed enhanced antifibrinolytic activity, prolonging lysis time by 522 ± 166 sec compared with 195 ± 105 sec for control protein (n = 12; p = 0.04). C3 from diabetes patients, which showed glycation of multiple lysine residues, demonstrated greater inter-individual variability in lysis prolongation compared with control protein (5–51% and 5–18%, respectively). Peptide microarray screening identified 2 peptide motifs within fibrinogen β chain (residues 424–433, 435–445) that interact with C3, suggesting these are C3-fibrinogen interaction sites. One fibrinogen-binding NABP resulted in complete abolition of C3 induced prolongation of lysis (728 ± 25.1 seconds to 632 ± 23.7 seconds, p = 0.005) and molecular modelling predicted that NABP binds fibrinogen in an area adjacent to C3-fibrinogen interaction sites. Conclusion/Interpretation: C3 from patients with diabetes has enhanced antifibrinolytic properties and displays large inter-individual variability. Fibrinogen β-chain represents one binding site with C3 and inhibition of fibrinogen-C3 interaction using NABP may help to identify novel therapeutic targets for reduction of thrombosis risk in diabetes.